Implementation Of Compress Therapy (Aloevera) In Pre-School Children With Hyperthermia Due To Dengue Hemorrhagic Fever At Arjawinangun Hospital, Cirebon Regency - Yanti, Rahma Sri; Sekriptini, Ayu Yuliyani; Zaitun, Zaitun (Jurnal Medisci, 2025)
Background: Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus that often attacks children, especially in preschool-age children. Children who experience DHF will exhibit signs and symptoms such as hyperthermia. One of the non-pharmacological methods that can be used to reduce hyperthermia in children is with compresses (aloe vera). Aims. To explore the implementation of compress therapy (aloe vera) as a non-pharmacological intervention to reduce hyperthermia in preschool-aged children diagnosed with DHF. Methods: The research design used was descriptive, rather than a case study approach, with two pre-existing children. Schools that experience hyperthermia due to DHF. Compress intervention (aloe vera) will be given for five days, with a duration of 15 minutes. Results: The study was conducted on pre-school children. Both have the same medical diagnosis, i.e., DHF. The intervention was in the form of compress therapy (aloe vera). After 5 days of intervention on both subjects, there was a change: Subject 1 experienced a decrease in body temperature on the third day, while Subject 2 experienced a reduction on the second day. Conclusion: The implementation of compress therapy (aloevera) has been proven to lower body temperature in preschool-aged children with hyperthermia due to DHF. Implementation. Aloe vera can be used as an alternative to non-pharmacological interventions that are safe, natural, and easy to apply.